Carcinomas With Concurrent Involvement of the Endometrium and Uterine Adnexa—Implications for Pathological Diagnosis and Clinical Management in Current Practice. Issue 5 (September 2022) - Singh, Naveena; Tinker, Anna; Gilks, C. Blake
Abstract: A proportion of endometrial and adnexal carcinomas have concurrent involvement of the other site. In the case of high-grade serous carcinomas involving the tubal epithelium as well as endometrium, distinction of tubo-ovarian high-grade serous from endometrial serous carcinoma can have implications for surgical as well as nonsurgical treatment approaches, including targeted therapies and referral to clinical genetics services. The other situation is involvement of the endometrium and ovary by low-grade endometrioid carcinoma; here separation of high-stage endometrial carcinoma from 2 low-stage, low-grade tumors determines adjuvant treatment decisions. These challenging scenarios are illustrated with case presentations and criteria for pathological reporting while acknowledging uncertainty where this is warranted. It is accepted that these are areas in transition, and any criteria offered are likely to change in the light of new information.